Surgical procedures in patients with haemophilic arthropathy of the ankle - Barg, Alexej; Schneider, Stefan W. (Haemophilia, 2016)
Background In haemophilia, the ankle joint is one of the most common and earliest joints affected by recurrent bleeding, commonly resulting in end-stage ankle osteoarthritis during early adulthood. The surgical treatment of haemophilic ankle arthropathy is challenging. Purpose This review aims to highlight the literature addressing clinical outcomes following the most common approaches for different stages of haemophilia-induced ankle osteoarthritis: arthroscopic debridement, joint distraction arthroplasty, supramalleolar osteotomies, total ankle replacement, and ankle arthrodesis. Methods A systematic literature review was performed using established medical literature databases. The following information was retrieved from the literature: patients’ demographics, surgical technique, duration of follow-up, clinical outcome including pain relief and complication rate. Results A total of 42 clinical studies published between 1978 and 2015 were included in the systematic literature review. Eight and 34 studies had prospective and retrospective design, respectively. The most common studies were level IV studies (64.3%). Discussion The orthopaedic treatment of patients with haemophilic ankle osteoarthritis is often challenging and requires complete and careful preoperative assessment. In general, both joint-preserving and joint non-preserving procedure types can be performed. All specific relative and absolute contraindications should be considered to achieve appropriate postoperative outcomes. Conclusion The current literature demonstrated that orthopaedic surgeries, with appropriate indication, in patients with haemophilic ankle arthropathy result in good postoperative results comparable to those observed in non-haemophiliacs. The surgical treatment should be performed in a setting with the ability to have multidisciplinary management, including expertise in haematology.
Gesehen am 29.04.2019